2019
DOI: 10.1111/1759-7714.13288
|View full text |Cite
|
Sign up to set email alerts
|

Aortic dissection in a patient treated with anlotinib for metastatic lung squamous cell carcinoma

Abstract: Anlotinib is an anti-angiogenic drug that targets vascular endothelial growth factor receptor, platelet-derived growth factor receptor, fibroblast growth factor receptor, c-Kit, and other kinases and has been approved for the treatment of advanced non-small cell lung cancer (NSCLC). As in other small-molecule tyrosine kinase inhibitors, adverse effects such as hypertension and cardiotoxicity may be seen. However, the relationship between anlotinib and aortic dissection has not been previously reported. Here, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Hence, anlotinib induced endothelial dysfunction and hypertension in our patient, who had no history of hypertension, may both contributed to PRES. Accordingly, in reviewed cases, we found that anlotinib occasionally increase blood pressure in those who had no history of hypertension, which simultaneously happened with vascular involved adverse effects ( 6 , 8 , 10 ). Discontinuation of anlotinib and anti-hypertensive drug could control increased blood pressure.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Hence, anlotinib induced endothelial dysfunction and hypertension in our patient, who had no history of hypertension, may both contributed to PRES. Accordingly, in reviewed cases, we found that anlotinib occasionally increase blood pressure in those who had no history of hypertension, which simultaneously happened with vascular involved adverse effects ( 6 , 8 , 10 ). Discontinuation of anlotinib and anti-hypertensive drug could control increased blood pressure.…”
Section: Discussionmentioning
confidence: 96%
“…A study reporting the phase I clinical trial outcomes for this drug found that the safety dosage is 12 mg/day (4) and that the most common adverse effects related to nervous system disorder was reported to be dizziness and headache in the ALTER0303 trial (5). In addition, there are a few rare adverse effects reported (6)(7)(8)(9)(10). Though there have been cases of PRES induced by other VEGF inhibitors, anlotinib has not been previously reported to be associated with PRES (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…Anlotinib is a novel small molecule, multitargeted tyrosine kinase inhibitor that is currently included in clinical trials for a variety of cancers. Its targets of action include significant inhibitory activity against angiogenesis‐related kinases such as VEGFR1/2/3, FGFR1/2/3 and other tumor‐associated kinases such as PDGFR, c‐Kit and Ret that are associated with cell proliferation; other partial kinase targets under malignant investigation include Aurora‐B, c‐FMS, and DDR1, and partial kinase mutants, such as PDGFR , c‐Kit , Met , and EGFR , and the inhibitory activity of anlotinib against partial mutants has been found to be even stronger than that of wild‐type 7–9 . The probability of EGFR ‐sensitive mutations in Chinese patients with advanced lung adenocarcinoma is about 50%.…”
Section: Discussionmentioning
confidence: 99%
“…The review of the literature identified seventeen eligible case reports with VEGFI related to AD (Aragon-Ching et al, 2008;Edeline et al, 2009;Carles, 2010;Formiga and Fanelli, 2014;Kurtz et al, 2014;Niwa et al, 2015;Koda et al, 2016;Hatem et al, 2017;Xu et al, 2017;Atsunori et al, 2018;Takada et al, 2018;Toru et al, 2018;Fubo and Gong, 2019;Zenoni et al, 2019;Jiang et al, 2020;Nikai et al, 2020;Ting and Lo, 2021). Thirteen of the seventeen patients are male, and four patients are female.…”
Section: Case Reports Collectionmentioning
confidence: 99%